Screening for hereditary haemocromatosis - Nadakkavukaran, I.; Gan, E.; Olynyk, John (Taylor and Francis, 2012)
Hereditary haemochromatosis (HH) is a common autosomal recessive disorder of iron overload in Caucasian populations. Clinical manifestations usually occur in individuals homozygous for the C282Y mutation in the HFE gene product and who have developed significant iron loading. Current screening methods can detect affected individuals either prior to or early during disease evolution, enabling early introduction of phlebotomy treatment that can normalise life expectancy. Evaluation of possible iron overload, via measurement of serum transferrin saturation and ferritin level, is the most appropriate initial test for those subjects presenting clinically for evaluation. HFE genotyping, when combined with serum biochemical measurements, defines the presence of likely iron overload and the underlying genetic disorder and is the preferred initial screening modality for families of an affected individual.Definitive proof of iron overload requires measurement of hepatic iron concentration or total iron burden via therapeutic phlebotomy; elevated serum ferritin level alone is not adequate. We now recognise that the natural history of HH is not as discrete as previously believed, because genetic and environmental modifiers of disease penetrance are increasingly identified as influencing the clinical expression of HH. In fact, a minority of C282Y homozygotes develop classical ‘iron overload disease’, although it has recently emerged that the disorder may predispose to breast and colorectal cancer. Uncertainties as to the true clinical impact of the condition at a population level lead to current recommendations of cascade screening of families of affected patients, case-finding in high-risk groups, such as patients with clinical manifestations consistent with the diagnosis, and a high level of clinical awareness in the community to facilitate early diagnosis. Generalised population screening is not presently recommended.